FORMULATION AND EVALUATION OF MULTIPURPOSE HERBAL CREAM - NAVINDGIKAR, NIKHIL NITIN; KAMALAPURKAR, K. A.; CHAVAN, PRASHANT S. (International Journal of Current Pharmaceutical Research, 2020)
Objective: To formulate and evaluate herbal cream using Aloe Vera gel, dimethyl sulphoxide extracts of Neem (Azadirachta indica) and Tulsi (Ocimumtenuiflorum) to give multipurpose effect. Methods: The cream was prepared by using the cream base that is bee’s wax, liquid paraffin, borax, methylparaben, distilled water, rose oil, Aloe Vera gel, dimethyl sulphoxide extracts of Neem and Tulsi. The cream was prepared by using the slab technique/extemporaneous method for geometric and homogenous mixing of all the excipients and the herbal extracts. By using slab technique, we have developed three batches of our herbal cream, namely F1H, F2H, and F3H. All three batches were evaluated for different parameters like appearance, PH, viscosity, phase separation. Results: All the three formulations F1H, F2H, F3H showed good appearance, PH, adequate viscosity and no phase separation was observed. Also, the formulations F1H, F2H, F3H showed no redness, erythema and irritation during irritancy study and they were easily washable. All the three formulations F1H, F2H, F3H were stable at room temperature. Conclusion: All three herbal ingredients showed significant different activities. Based on the results, we can suggest that all the three formulations F1H, F2H, F3H were stable and can be safely used on the skin.